Effect of sulfate radical-based oxidation pretreatments for mitigating ceramic UF membrane fouling caused by algal extracellular organic matter. (15th November 2018) - Cheng, Xiaoxiang; Wu, Daoji; Liang, Heng; Zhu, Xuewu; Tang, Xiaobin; Gan, Zhendong; Xing, Jiajian; Luo, Xinsheng; Li, Guibai
Abstract: Algal extracellular organic matter (EOM) released from Microcystis aeruginosa can cause severe membrane fouling during algae-laden water treatment. To solve this problem, three typical sulfate radical-based advanced oxidation processes (SR-AOPs), i.e., ferrous iron/peroxymonosulfate (Fe(II)/PMS), UV/PMS and UV/Fe(II)/PMS, were employed as membrane pretreatment strategies. Their performance on mitigating EOM fouling of a ceramic UF membrane was systematically investigated and compared in the present study. The results indicated that SR-AOPs pretreatments could promote the reduction of DOC and UV254, and the removal performance showed an apparent regularity of UV/Fe(II)/PMS > Fe(II)/PMS > UV/PMS. The pretreatments were very effective for decomposing high-MW biopolymers (>20, 000 Da) into low-MW humic substances (1000–20, 000 Da), thus reducing the accumulation of high-MW biopolymers on membrane surface. With respect to membrane fouling control, Fe(II)/PMS significantly mitigated both reversible and irreversible membrane fouling, whereas UV/PMS only reduced reversible fouling, and exhibited little effect on irreversible fouling. By contrast, UV/Fe(II)/PMS showed the best performance for fouling reduction due to the synergistic effect of UV and Fe(II) for PMS activation. The dominating fouling mechanism was governed by both pore blockage and cake filtration, likely due to the bimodal MW distribution of EOM, and SR-AOPs pretreatments delayed the transition from pore blockage to cake filtration. In addition, SR-AOPs prior to UF membrane were also very effective to improve the removal of micropollutants (i.e., ATZ, SMT and p -CNB). These results demonstrate the potential application of SR-AOPs as pretreatment for membrane fouling control during algae-laden water treatment. Graphical abstract: Image 1 Highlights: SR-AOPs pretreatments were used to control EOM fouling of a ceramic UF membrane. Fe(II)/PMS reduced reversible and irreversible fouling by oxidation and coagulation. UV/PMS mitigated reversible fouling by oxidative decomposing of high-MW biopolymers. UV/Fe(II) showed synergistic effect for PMS activation thus greatly reduced fouling.